Where Are the Months? Mental Images of Circular Time in a Large Online Sample - Laeng, Bruno; Hofseth, Anders (Frontiers in Psychology, 2019)
People may think about time by mentally imaging it in some spatial form, or as ‘spacetime’. In an online survey, 76,922 Norwegian individuals positioned two dots corresponding to the months of December and March on what they imagined to be their appropriate places on a circle. The majority of respondents placed December within a section of the circumference ranging from 11:00 to 12:00 o’clock, but a group of respondents chose positions around the diametrically opposite 6:00 o’clock position. A similar relationship occurred for March, where most respondents chose a position ranging from 2:30 and 3:00 o’clock but a group of respondents chose positions around 9:00 o’clock. About half of respondents (N = 39,797) continued to fill out an online questionnaire probing their mental images related to the ‘year’ concept. This clarified that 75% of respondents “saw” the months unfolding in a clockwise direction versus 19% in a counter clockwise fashion. Moreover, while a majority (70%) stated that they imagined the year as a ‘circle’, the rest indicated the use of other mental images (e.g., ellipses and spirals, lines and squares, idiosyncratic or synaesthetic spatial forms). We found only weak effects or preferences for spatial forms based on respondents’ gender, handedness, age or geographical location.